Exosomes' profile in ankylosing spondylitis: A preliminary study - ABACAR, KEREM YİĞİT; ATAGÜNDÜZ, MEHMET PAMİR; ERZİK, CAN (My University, 2023)
Objective: Ankylosing spondylitis (AS) is a chronic systemic inflammatory disease that leads to structural and functional im-pairments and reduced quality of life, with heterogeneous manifestations. The origin and possible role of extracellular vesicles represented by exosomes (EVexo) in the pathogenesis of AS were examined in this study. Materials and Methods: Extracellular vesicles (EVs) were isolated from serum from ten AS patients and ten healthy controls through Izon qEV2/35 nm columns. After assessing the isolate purity by bicinchoninic acid assay (BCA) and Enzyme-Linked ImmunoSorbent Assay (ELISA), the relationship between EVexo concentration and AS was tested by the BCA method. The EVexo surface markers were analyzed by flow cytometry (FC) to verify EVexo presence and reveal its origin. Results: In FC analysis, CD86+TSG101+ and CD3+TSG101+ exosome percentages of AS group were significantly higher than the control group (p<0.05). A significant difference was found between the AS and control groups in terms of CD3+IL17+ and CD3+IFNg+ and CD86+TNF alpha+ and CD86+IL12(p35)+ exosome percentages (p<0.01). Conclusion: The exosomes whose ratio increased in the AS process were derived from T cells expressing increased levels of IL-17A and IFNg in their membranes, and macrophages expressing increased levels of TNF alpha and IL-12(p35) in their membranes. The EVexo profile did not change according to the AS course.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; TIP, GENEL & DAHİLİ; Klinik Tıp; Klinik Tıp (MED); MEDICINE, GENERAL & INTERNAL; CLINICAL MEDICINE; Clinical Medicine (MED); Genel Sağlık Meslekleri; Patofizyoloji; Temel Bilgi ve Beceriler; Değerlendirme ve Teşhis; Dahiliye; Aile Sağlığı; Tıp (çeşitli); Genel Tıp; General Health Professions; Pathophysiology; Fundamentals and Skills; Assessment and Diagnosis; Internal Medicine; Family Practice; Medicine (miscellaneous); General Medicine; Exosome; extracellular vesicle; ankylosing spondylitis; cell surface markers